OVERROTECTVE MOTHER IN JODDI PICOULT’S NOVEL, MY SISTER’S KEEPER - Nur Atikah Ridwan; Zulfan Sahri (Universitas Islam Sumatera Utara, 2020)
The objectives of this study are to reveal the causes and negative impacts of overprotective mother’s attitude towards her child in the best-selling novel entitled My Sister's Keeper by Jodi Picoult, and to see how overprotective Sara Fitzgerald as a mother who has an overprotective attitude towards her second child. This research uses descriptive qualitative method with library study to find out the overprotective mother and how the overprotective developed by applying internal and external overprotective theory and mother's theory. The primary data used is the novel itself. Secondary data are books and articles relating to conflict theory. The results showed that there was a major problem that caused by Sara Fitzgerald as an overprotective mother and the impact of her overprotective attitude towards her daughter. There are two causes that Sara becomes an overprotective mother to her second daughter: her illness and her recovery and the impact towards her third daughter is lacking affection and suffering.